Fracking Lancashire: The planning process, social harm and collective trauma. Issue 98 (January 2019) - Short, Damien; Szolucha, Anna
Abstract: To date there have been very few studies that have sought to investigate the crimes, harms and human rights violations associated with the process of 'extreme energy', whereby energy extraction methods grow more 'unconventional' and intense over time as easier to extract resources are depleted. The fields of rural sociology and political science have produced important perception studies but few social impact studies. The field of 'green criminology', while well suited to examining the impacts of extreme energy given its focus on social and environmental 'harms', has produced just one citizen 'complaint' study to date. It is vital that more social and environmental impact studies become part of the local, national and international public policy debate. To this end, in the following paper we seek to move beyond perception studies to highlight the harms that can occur at the planning and approval stage. Indeed, while the UK is yet to see unconventional gas and oil extraction reach the production stage, as this article shows, local communities can suffer significant harms even at the exploration stage when national governments with neoliberal economic agendas are set on developing unconventional resources in the face of considerable opposition and a wealth of evidence of environmental and social harms. This paper takes a broad interdisciplinary approach, inspired by green criminological insights, that shows how a form of 'collective trauma' has been experienced at the exploration stage by communities in the North of England.